Integrative Analysis of MALT1 as a Potential Therapeutic Target for Prostate Cancer and its Immunological Role in Pan-Cancer - Tan, Haotian; Xie, Yaqi; Zhang, Xuebao; Wu, Shuang; Zhao, Hongwei; Wu, Jitao; Wang, Wenting; Lin, Chunhua (Frontiers in Molecular Biosciences, 2021)
Background: Mucosa-associated lymphoma antigen 1 (MALT1) is an oncogene in subsets of diffuse large B cell lymphoma (DLBCL) and mucosa-associated lymphoid tissue type (MALT) lymphoma. However, the role of MALT1 across cancers, especially in prostate cancer is still poorly understood. Methods: Here, we used several public datasets to evaluate MALT1 expression. Then, PCa cell lines and nude mice were used to investigate the cellular functions in vitro and in vivo. Microarray data were downloaded from The Cancer Genome Atlas and MALT1 was subjected to gene set enrichment analysis (GSEA) and Gene Ontology (GO) analysis to identify the biological functions and relevant pathways. Additionally, the correlations between MALT1 expression and mismatch repair (MMR) gene mutation, immune checkpoint gene expression, tumor mutational burden (TMB), and microsatellite instability (MSI) were investigated by Pearson correlation analysis. Moreover, the correlation between MALT1 expression and tumor immune infiltration was analyzed by the Tumor Immune Evaluation Resource (TIMER) database. Results: MALT1 overexpression was significantly correlated with MMR gene mutation levels and crucially promoted proliferation and colony genesis while reducing PCa cell apoptosis levels in vivo and in vitro. MALT1 expression showed strong correlations with immune checkpoint genes, TMB, and MSI in most cancers. The GO analysis indicated that MALT1-coexpressed genes were involved in heterotypic cell-cell adhesion, actin filament-based movement regulation, and action potential regulation. GSEA revealed that MALT1 expression was associated with several signaling pathways, including the NF-κB signaling, Wnt/β-catenin and TGF-β signaling pathways, in PCa. Additionally, MALT1 expression was significantly correlated with the infiltration of immune cells, including B cells, CD8+ T cells, dendritic cells and macrophages, and negatively correlated with CD4+ cell infiltration in PCa. Conclusion: MALT1 expression is higher in pancancer samples than in normal tissues. MALT1 promoted proliferation and colony genesis while reducing PCa cell apoptosis levels, and MALT1 suppression could inhibit xenograft tumor establishment in nude mice. Furthermore, MALT1 expression is closely related to the occurrence and development of multiple tumors in multiple ways. Therefore, MALT1 may be an emerging therapeutic target for a variety of cancers especially PCa.